Analysis of genetic diversity in Portuguese Ceratonia siliqua L. cultivars using RAPD and AFLP markers - Barracosa, P.; Lima, M.B.; Cravador, A.
Although carob (Ceratonia siliqua L.)is of great economic importance little is still known about the pattern of genetic variation within this species. Morphological characteristics based on 31 fruit and seeds of continuous characters determinant for agro-industrial uses, were compared with RAPD and AFLP markers for assessing genetic distances in 68 accessions of carob trees, from different cultivars, varieties and eco-geographic regions of Algarve. Eighteen selected RAPD primers applied to the 68 accessions produced a total of 235 fragments ranging from 200 to 2000 bp, of which 93 (40
Keywords: RAPD; AFLP; GENETIC DIVERSITY; CAROB; CERATONIA SILIQUA; LEGUMINOSAE